Study of Morphological, Optical and Electrical Properties of Graphene Oxide Thin Film Relative to the Reaction Time of Synthesis - Jaafar, E.; Kashif, M.; Sahari, S.K.; Ngaini, Zainab (Universiti Teknikal Malaysia Melaka, 2018)
In this work, graphene oxide (GO) was synthesized by treating graphite powder with potassium permanganate (KMnO4) and a mixture of concentrated sulphuric acid (H2SO4)/ phosphoric acid (H3PO4) at various reaction time. The GO thin film is coated on a glass substrate by using drop casting method. The morphological, optical and electrical properties of GO thin film were carried out by using scanning electron microscopy (SEM), UV-Vis spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscopy (FTIR), and current-voltage (I-V) characteristic. The morphological study of GO shows that more oxygen functional groups were observed as the reaction time increases from 24h to 96h and is justified from the optical properties of GO thin films. The optical and morphological properties of GO thin film affects the electrical properties as the resistivity increase from 9.33 x 106Ω.cm to 26.15 x 106Ω.cm. Morphological and optical data confirms that 48h is the optimized reaction time having a resistivity of 12.30 x 106Ω.cm.